The Mediating Role of Financial Inclusion in the Relationship between Financial Literacy and MSME Performance - Fahri Haikal; Diin Fitri; Agung Priyono; Narti Eka Putri (Journal of Business and Behavioural Entrepreneurship, 2025)
MSMEs play a strategic role in the Indonesian economy but still face obstacles in the form of low financial literacy and limited access to formal financial services. This study uses a quantitative approach involving 200 MSME actors in Jakarta selected through purposive sampling, where data were collected using questionnaires and analysed using a Partial Least Squares (PLS-SEM) structural equation model. The results show that financial literacy has a positive and significant effect on financial inclusion and SME performance. Financial inclusion also has a positive and significant effect on SME performance and mediates the relationship between financial literacy and SME performance, with a stronger indirect effect than a direct effect. These findings emphasise the importance of improving financial literacy, followed by expanding access to formal financial services so that SMEs can improve their performance and competitiveness.